Penerepan Metode Bermain Peran (Role Play) Dalam Meningkatkan Minat Belajar Siswa Pada Mata Pelajaran IPS Kelas IV DI SDN 173249 Sibulan- Bulan - Lina Adinda Krismasuci Hutabarat, Julia ivanna (Journal of Educational Research and Humaniora (JERH), 2023)
In an educational context, student interest in learning is very important, because high interest will motivate students to learn more enthusiastically and have a positive impact on achieving learning outcomes Role playing is a learning strategy that involves students in imaginary situations where they take on certain roles or characters. related to Social Studies (Social Studies) class IV. This study uses a Classroom Action Research (CAR) approach. The data collection techniques used in this study were observation, tests, and documentation. The research instruments were teacher observation sheets, student observation sheets, and evaluation question sheets.